Sustainability Balanced Scorecard: an Alternative to Apply Legitimacy Theory - Pertiwi, Imanda Firmantyas Putri; Hidayati, Isnaini Nur; Retno Meilani, Sayekti Endah; Rahmayati, Anim (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2019)
Purposes. Sustainability Balanced Scorecard (SBSC) is the development of balanced scorecard as a comprehensive company performance appraisal method, which the assessment focus on financial perspective, customer, internal business processes, growth and learning as well as the social and environmental perspective as an effort of sustainability. This sustainability effort is in line with the legitimacy theory, which states that the company should be run in accordance with the prevailing norms of the place where the company is located. Madukismo Sugar Company (PG. Madukismo) is a company that has potential environmental destruction is the subject of this research. This research is intended to provide an overview of PG Madukismo's performance evaluation using the SBSC method, whether it is able to explain the legitimacy theory.Method. The case study with a descriptive qualitative method by triangulation system becomes a method of this research development.Findings. Outlined, the performance of PG Madukismo shows good results, the financial perspective shows some improvement, profit has increased, as well as efficiency. The customer's perspective also shows satisfactory performance, the high level of customer retention and the minimum level of complaints is enough to explain. The internal business process perspective results are also satisfactory, innovation on production, sales and after-sales processes are considered good. A less encouraging perspective is the perspective of growth and learning, even though employee retention is good but the amount of employee training actually shows a downward trend. Last but not least, is a social and environmental perspective. The results obtained were quite surprising, although in 2016 the news about Madukismo waste management was less pleasant, in 2018 Madukismo was able to improve its waste management and get a positive response from surrounding communities who said that the stench from Madukismo waste continued to decrease.Implication. This research gives insight and detail of how to assess a company using five perspectives of SBSC to prove that legitimacy theory can be applied and bringing the hope of sustainable business.Keyword: Sustainability Balanced Scorecard, green accounting, social and environmental, PG.Madukismo